Examining the determinants of mobile commerce adoption through UTAUT: a structural equation modelling - Barry, Moussa; Haque, A. K. M. Ahasanul (Otago Polytechnic, 2024)
Abstract: In the past couple of decades, there has been a substantial improvement in mobile commerce development. Despite the development of mobile commerce, its adoption rate is still low in Malaysia compared to other countries in the region, such as Indonesia, Thailand, and the Philippines. This study aims to examine the determinants of mobile commerce adoption among users in Malaysia. This study introduces novel research that offers a complete perspective on the unified theory of acceptance and use of technology (UTAUT) and its correlation with perceived trust in mobile commerce transactions. This study used a convenient sampling by employing a survey from consumers in Malaysia with certain criteria. The study also employed structural equation modelling (SEM) based on analysis of momentum structure (AMOS). The findings showed that the adoption intention of mobile commerce is significantly influenced by perceived trust, performance expectancy, and effort expectancy. Furthermore, the adoption of mobile commerce is greatly affected by the adoption intention of mobile commerce and the facilitating conditions. This study provides an understanding of perceived trust and the adoption of mobile commerce among consumers in Malaysia. We suggest that mobile commerce providers improve their platforms and services to enhance the adoption rate of mobile commerce in Malaysia.